Anisotropic Superelastic and Shape Memory Effect of Nitinol Manufactured by Electron Beam Powder Bed Fusion - Fink, Alexander; Wahlmann, Benjamin; Körner, Carolin (Advanced Materials & Sustainable Manufacturing, 2024)
This study explores the impact of energy input and build orientation on the anisotropic mechanical and functional properties of Ti-rich Nitinol (NiTi) produced via electron beam powder bed fusion (PBF-EB), integrated with layerwise in-situ monitoring of the melted surface via backscatter electron detection (ELO). NiTi, a binary alloy of nickel and titanium, exhibits shape memory and superelasticity, making it widely used in biomedical applications and sustainable technologies. PBF-EB, particularly with ELO, is highlighted for its advantages in producing crack-free NiTi with tailored microstructures. The investigation reveals that energy input significantly influences microstructure phases, with higher energy promoting increased evaporation of Ni and enhancing Ti-rich Ti2Ni precipitates, allowing for tailored material properties. Build orientation also proves crucial, impacting mechanical responses and functional properties. The 0° orientation yields the hardest mechanical response with the highest ultimate tensile strength (UTS) and the highest strain recovery ratio while the 45° orientation shows improved ductility but lower UTS. The influencing factors towards the formation of the anisotropic material properties are explained and the potential of tailoring the NiTi properties for specific applications by controlling energy input and build orientation in the PBF-EB process are underlined. These insights offer valuable criteria for designing innovative NiTi part
Keywords: Shape memory effect (SME); Superelasticity; Anisotropy; Nitinol (NiTi); Thermomechanical compression test; Electron Beam Powder Bed Fusion (PBF-EB); Electron-Optical Process Monitoring (ELO)

Bioinspired damage tolerant diamond-metal laminates by alternating CVD and PVD processes - Fromm, Timo; Bruns, Sebastian; Müller, Marie Christin; Fink, Alexander; Borchardt, Rudolf; Rosiwal, Stefan; Durst, Karsten (Materials & Design, 2022)
In this study, we present a novel process to fabricate diamond-metal laminates. By means of successive chemical vapor deposition and physical vapor deposition processes, the lamellar material is deposited layer by layer on silicon wafers. Laminates consisting of two, five and ten layers of diamond were realized. In addition, fabrication of diamond-based, biomimetic brick-and-mortar structures was successful for the first time. For this purpose, diamond layers of a five-layer laminate were structured by laser cutting into hexagonal platelets with diameters of 400 µm and 800 µm. The mechanical behavior was characterized by three-point bending. Mostly spontaneous failure with little crack deflection was observed, indicating a strong diamond-metal interface. At over 1250 MPa, the laminates exhibit nominal strengths that exceed those of other lamellar ceramic-metal composites by at least a factor of two, while fracture energy lies in a medium range. The laminates with segmented diamond layers exhibit damage tolerance.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Biomimetic materials; Ceramic laminates; Chemical vapor deposition (CVD); Diamond foil; Physical vapor deposition (PVD); Toughness

Functional properties and shape memory effect of Nitinol manufactured via electron beam powder bed fusion - Fink, Alexander; Fu, Zongwen; Körner, Carolin (Materialia, 2023)
Ti-rich Nitinol (NiTi) is characterized by its functional properties to restore its original shape after deformation due to a temperature-induced reversible martensitic phase transition. In this study, dense Ti-rich Nitinol free of cracks is successfully produced by means of Electron Beam Powder Bed Fusion (PBF-EB). The martensitic phase transition behavior of the as-built NiTi parts and powder is analyzed using Differential Scanning Calorimetry (DSC) analysis. To gain a deep understanding of the DSC results, segregation during solidification is thermodynamically studied (CALPHAD). The PBF-EB-fabricated NiTi shows a microstructure containing fine columnar grains and numerous precipitates, whose influence on the tensile properties at room temperature is discussed. Furthermore, the one-way and two-way shape memory effects of PBE-EB-produced NiTi are investigated using an innovative experimental setup based on thermomechanical training.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Martensitic phase transformation; NiTi; Powder bed fusion - electron beam (PBF-EB); Shape memory effect (SME); Thermal and mechanical cycling

Thermo-Mechanical Study on Auxetic Shape Memory Periodic Open Cellular Structures—Part I: Characterization of Reentrant Geometry and Effective Heat Conductivity - Rudolf, Dominik; Fink, Alexander; Körner, Carolin; Freund, Hannsjörg (Advanced Engineering Materials, 2024)
Periodic open cellular structures (POCS) are additively manufactured supports for heterogeneous catalysts in the field of chemical reaction engineering. Constructed from a repeated unit cell, POCS offer excellent heat transport characteristics due to heat conduction in the continuous solid matrix. However, when inserted into tubular reactors, a loose fit between structure and tube wall results. This considerably hinders heat transfer across the wall. The novel POCS concept presented in this work aims at an intensified wall heat transfer by utilizing a reentrant structure design to ensure auxetic behavior. If the POCS is made of shape memory alloy, it can recover its original shape. Combining these two effects with an initial radial oversize, an interference fit with the tube is established. This contribution comprises the geometric description of reentrant POCS and heat conduction simulations for characterization of the effective heat conductivity, yielding scaling correlations dependent on geometric parameters. Moreover, the effective radial heat conductivity of POCS in cylindrical shape is explicitly investigated. The influencing factor identified is the ratio of tube diameter and cell size: while the ratio increases, the effective radial heat conductivity decreases, but remains well above the effective heat conductivity of the unit cell.
CRIS-Team Scopus Importer:2024-11-29
Keywords: auxetic structures; effective heat conductivity; periodic open cellular structures; process intensification; structured catalysts

Thermo‐mechanical Study on Auxetic Shape Memory Periodic Open Cellular Structures—Part II: Mechanical and Shape Memory Properties - Fink, Alexander; Rudolf, Dominik; Wahlmann, Benjamin; Freund, Hannsjörg; Körner, Carolin (Advanced Engineering Materials, 2024)
This study explores the potential of periodic open cellular structures (POCS) that combine the auxetic and the shape memory effect (SME) with the aim of enhancing heat transfer in catalytic tubular reactors. On the one hand, these structures exhibit a negative Poisson's ratio, contracting perpendicular to the load axis under compression, driven by the rotation of nodes generating complex stress fields. On the other hand, the shape memory alloy (SMA) Nitinol (NiTi) with a reversible strain of up to 8% produced via electron beam powder bed fusion (PBF-EB) shows extraordinary material properties with a high degree of freedom in structure design. The study conducts finite element method simulations and experiments to design POCS with tailored properties. Compression tests on less expensive Ti-6Al-4V POCS compared to NiTi POCS validate the simulative parameter study applied to fabricate novel auxetic hexagonal reentrant structures from NiTi with a unique stacking order and curved struts. The aim of this part of the study is to offer a pathway to design a NiTi auxetic POCS based on validated simulations. Further, it explains the interactions between geometrical parameters and mechanical properties of cellular reentrant NiTi structures. An optimized auxetic NiTi POCS achieved a Poisson's ratio of −